Early prosociality is conditional on opportunity cost and familiarity with the target - Lee, Kristy Jia Jin (2023)
Developmental research in the past decade has painted the picture of a gregarious child ready to engage in a range of prosocial behavior, but less is known about the situational factors that moderate this behavior. The present study investigated the effects of cost and familiarity on children's readiness to help the victim of a moral transgression. Opportunity cost was operationalized as the time and effort expended on providing help, that could otherwise be used to earn a reward from a productive task. Familiarity varied as a function of whether there was prior contact between the child and victim. Five- and six-year-olds in Singapore (N = 120) witnessed an adult transgressor destroy the victim's tower of blocks, responded to the victim's pleas for help in rebuilding her tower, and shared resources with both actresses. Contrary to our initial predictions, children helped a familiar victim less when cost was high as opposed to low, but helped an unfamiliar victim equally regardless of cost. Additionally, helping rates were low (30–60%) except in the least prohibitive condition (> 80%; Low-Cost, Familiar Victim), stemming from a combination of not having a productive task to occupy one's time and energy, and simultaneously a familiar target which increased one's intrinsic motivation to help. The conditional limits imposed on children's decision to help thus appear to be, “I'll help, if I know you and have nothing better to do!” In terms of resource sharing, children behaved selfishly toward both the victim and transgressor regardless of their familiarity with the victim. Altogether, our findings suggest that children consider self-interest when deciding whether to help and share with others.